Names and Naming in Online Thrift Shop Based on Linguistic Anthropological Perspective - Ika Setyowati Sutedjo (MOZAIK HUMANIORA, 2021)
This study aims to examine names and naming in online thrift shops in Indonesia based on linguistic and anthropological perspectives. Names and naming as essential parts of language convey representation of an individual, object, places, etc. Names also have three categories in anthropological perspective, such as name and identity, roles of name, and name and culture. To pursue the goal of this study, qualitative descriptive method together with linguistic and anthropological perspectives was used. Next, purposive sampling technique was used to collect names of online thrift shops in Indonesia which have more than 500 followers on Instagram as criteria. In total, there were 50 names of online thrift shops in Indonesia collected. Interviewing all of the owners of online thrift shops selected then was conducted. The results showed that the owners of the selected online thrift shops have many considerations and reasons before choosing the suitable name for their small business, such as self-representation and social relationship with others. Those considerations represent the owner’s self-identity. In conclusion, names of online thrift shops reveal an identity of the owner as well as the role of those names in the society.